Fund managers - Why the best might be the worst: On the evolutionary vigor of risk-seeking behavior - Björn-Christopher Witte (Economics: The Open-Access, Open-Assessment E-Journal, 2012)
This article explores the influence of competitive conditions on the evolutionary fitness of different risk preferences. As a practical example, the professional competition between fund managers is considered. To explore how different settings of competition parameters, the exclusion rate and the exclusion interval, affect individual investment behavior, an evolutionary model is developed. Using a simple genetic algorithm, two attributes of virtual fund managers evolve: the share of capital invested in a risky asset and the amount of excessive risk accepted, where a positive value of the latter parameter points to an inefficient investment portfolio. The simulation experiments illustrate that the influence of competitive conditions on investment behavior and attitudes towards risk is significant. What is alarming is that intense competitive pressure generates risk-seeking behavior and undermines the predominance of the most skilled. In these conditions, evolution does not necessarily select managers with efficient portfolios. These results underline the institutional need for the creation of a competitive framework in which risk-taking does not provide an evolutionary advantage per se, and indicate measures on how to achieve this.
Keywords: C73; D81; G11; G24; 330; risk preferences; competition; genetic programming; fund managers; portfolio theory; Investmentfonds; Führungskräfte; Anlageverhalten; Risikopräferenz; Wettbewerb; Evolutionsökonomik; Evolutionärer Algorithmus; Theorie